Teknik penderiaan jauh dalam kaji~ sedimen terampai di muara Sungai Langat - Suraya Sharil; Othman A. Karim; Sharifah Mastura Syed Abdullah (2005)
This study examines the sediment plume behaviour entering the sea using the physical model and remote sensing techniques. This paper will only discuss the application of remote sensing in suspended sediment study at Sg. Langat estuary. CIMEL radiance meter was used as a sensor to record optical data (digital count value or DN) from the simulation of the sediment plume dispersion in the model. This study observes the relationship between the DN obtained with the suspended sediment concentration. Results from correlation analysis show that the relation between DN and sediment plume concentration in the lab is most significant and strong at 0.85 μm wavelength, and the weakest relation is in the 0.45 μm wavelength. Small water particles from the wave generation were identified as one of the most important atmospheric disturbance to optical data, especially for shorter wavelength i.e. 0.45 μm. Beside that, water roughness and additional illumination from the 1000 watt spotlight also affect the DN values obtained. Water roughness has caused the increase in the DN value, while illumination from spotlight has caused a shift in the peak of spectral signature to longer wavelength, i.e. 0.85μm